Re-evaluating resilience: from individual vulnerabilities to the strength of cultures and collectivities among indigenous communities. Issue 2 (3rd May 2016) - Thomas, Darren; Mitchell, Terry; Arseneau, Courtney
Abstract: Current conceptual approaches to understanding indigenous resilience as an individual trait, as a predisposition to succeed despite adversity, fails to acknowledge the political, social, economic and environmental realities of indigenous communities and misdirects the responsibility away from governments and colonial policies and onto the individuals themselves. We seek to reformulate a concept of indigenous resilience that is not viewed as an internalised, individual attribute, but rather as the strength and power of the collective, cultural knowledge of indigenous communities. Despite centuries of colonial interference, indigenous knowledge and cultures have endured. We posit that it is the resilience of indigenous knowledge and the re-emergence of indigenous ways of knowing that will inform and invigorate the re-conscientisation and liberation of indigenous peoples in reclaiming and advancing the physical, mental, emotional, and spiritual health and well-being of their Nations.